2020
DOI: 10.1038/s41419-020-02796-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of lncRNA SH3PXD2A-AS1 with preeclampsia and its function in invasion and migration of placental trophoblast cells

Abstract: Accumulating evidence suggests that the pathogenesis of preeclampsia involves poor placentation caused by insufficient trophoblast invasion and impaired uterine spiral artery remodeling, yet the underlying molecular mechanism remains unclear. We carried out transcriptome profiling on placentae from preeclamptic patients and normal subjects, and identified about four hundred long non-coding RNAs differentially expressed in placentae of patients with early-onset severe preeclampsia. Here, we report our identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 73 publications
(71 reference statements)
0
17
0
Order By: Relevance
“…Increasing evidence has revealed the key roles of lncRNAs in proliferation, survival, angiogenesis, migration, and cancer cell invasion [ 69 ]. In the last few years, functional studies on well-characterized choriocarcinoma cell lines representing villous and extravillous trophoblast phenotype (BeWo, JAR, and JEG-3), first-trimester trophoblast cell lines (HTR-8/SVneo and Swan-71), and primary trophoblast cell cultures reported some lncRNAs involved in regulatory mechanisms in trophoblasts activity, such as H19, HOTAIR, MALAT1, SPRY4-IT1, and MEG3 [ 70 ]. The potential mechanisms underlying the action of these and others lncRNAs in trophoblasts will be discussed in each pathology to elucidate the potential role of these molecules.…”
Section: Etiopathogenesis Of Placental Related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has revealed the key roles of lncRNAs in proliferation, survival, angiogenesis, migration, and cancer cell invasion [ 69 ]. In the last few years, functional studies on well-characterized choriocarcinoma cell lines representing villous and extravillous trophoblast phenotype (BeWo, JAR, and JEG-3), first-trimester trophoblast cell lines (HTR-8/SVneo and Swan-71), and primary trophoblast cell cultures reported some lncRNAs involved in regulatory mechanisms in trophoblasts activity, such as H19, HOTAIR, MALAT1, SPRY4-IT1, and MEG3 [ 70 ]. The potential mechanisms underlying the action of these and others lncRNAs in trophoblasts will be discussed in each pathology to elucidate the potential role of these molecules.…”
Section: Etiopathogenesis Of Placental Related Diseasesmentioning
confidence: 99%
“…Numerous reports have described the aberrant expression of lncRNAs in plasma or placentae samples collected from women with PE ( Figure 1 ). For instance, the lncRNA SH3PXD2A-AS1, which was found upregulated in term placentae from PE women, is reported to be involved in placenta development by recruiting the CCCTC-binding factor (CTCF) to the promoter regions of SH3PXD2A and CCR7, thus inhibiting the transcription of these two essential factors that are involved in invasion and migration of early trophoblast cells [ 70 ]. Another lncRNA described as upregulated in placentas from PE patients is the lncRNA H19 [ 72 ].…”
Section: Lncrnas In Preeclampsiamentioning
confidence: 99%
“…Among those, hsa_circ_0019868 [SH3 and PX domain-containing protein 2A (SH3PXD2A) gene] may be associated with MPP pathogenesis. SH3PXD2A is an adapter protein involved in the invasiveness of cancer cells that mediates the neurotoxic effect of the amyloid-β peptide (37). The higher expression in MPP groups may enhance the invasiveness of M. pneumoniae.…”
Section: Relative Gene Expression Levelsmentioning
confidence: 99%
“…Clinical and pathological studies previously confirmed that placental dysplasia, excessive maternal inflammation and endothelial dysfunction are central to the pathogenesis of PE ( 2 , 5 ). Accumulating evidence has also shown that the etiology of PE involves poor placentation due to inadequate trophoblast invasion ( 6 , 7 ). Therefore, it is imperative to perform preclinical experiments in trophoblasts to elucidate the mechanism underlying PE pathogenesis.…”
Section: Introductionmentioning
confidence: 99%